THE PHONOLOGICAL SYSTEM OF SASAK DIALECT SPOKEN IN MATARAM; A DESCRIPTIVE STUDY - Yuwanda, Yati (International Journal of Language and Literature, 2017)
The research aimed to describe vowels and consonants in Sasak dialect. This research is descriptive qualitative research. The object of this research is the phological system of Sasak dialect about vowel and consonant while the object of this research is people in Mataram city especially in rembige village, Nusa Tenggara Barat. The subject took from the observation technique. They are selected from the characteristics of fluent Sasak dialect. The data collected from three different domains. The domain are family domain, friendship domain and neighborhood domain. The theory to analyze the data was from Miler and Huberman (1984). Instrument collected from observation and recording technique, the result of this research shows that the type of vowels in Sasak dialect are /Ê/, /Éª/, /u/, /e/, /o/ and /É/. The vowel / i /Â Â  had two allophones namely [ Éª ] and [ i ]. the vowel / e /Â Â  had two allophones namely [e] and [É],Â  the vowel /o/ had one allophone namely [o] and the vowel / u / also had one allophones [ u ]. There were 18 consonants found in Sasak Dialect, those were: /b/, /c/, /d/, /g/, /h/, /j/, /k/, /l/, /m/, /n/, /p/, /q/, /r/, /s/, /t/, /w/, /y/, /Å/, and /Ã±/.